Taxonomy of Defects in Auxiliary Elements of Facades and Its Relation with Lawsuits Filed by Property Owners - Manuel J. Carretero-Ayuso; Carlos E. Rodríguez-Jiménez; Maria Teresa Pinheiro-Alves; Enrique Fernández-Tapia (Buildings, 2022)
While at first it can be thought that the auxiliary elements of facades are merely ornamental with little practical function, this study shows that these components of the building envelope have a high impact on the envelope’s functioning and performance. This is carried out through the analysis of all relevant lawsuits filed in Spain over a 10 year period, a data set in which a surprisingly high number of 1033 cases of defects was found to affect external windowsills, exterior wainscots or cornices (the three auxiliary elements considered) was found. Considering the total number of lawsuits, this is an objectively unprecedented study. An analysis is carried out regarding the interrelations between elements, defects, causes, and types of buildings, with the aim of obtaining a sorted classification of the data. This constitutes a useful tool to prevent future problems arising from either the design, execution, or maintenance of facades. These include various issues resulting from humidities, one of the most frequent envelope defects, which are found to significantly affect the auxiliary elements of facades.